ISTILAH KEKERABATAN DALAM BAHASA INGGRIS DAN BAHASA TALAUD (SUATU ANALISIS KONTRASTIF) - Padu, Jeiner; Jansen, Frieda Th.; Lotulung, Donald R. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â ABSTRACT This research is an attempt to describe and analyze the kinship terms in English and Talaud Language. The problems of this research namely â€œwhat are the kinship terms in English and Talaud language and what are the similarities and differences of both languages.â€ The method which used in this research is descriptive method. The theory which used in this research are Burlingâ€™s and Lounsburryâ€™s theories to analyze the kinship terms, and Ladoâ€™s theory to contrast both languages. The English data were taken from sociolinguistic books especially about kinship terms, internet and previous thesis about kinship terms that have been done before, whereas the data about the kinship terms in Talaud language were collected from the informants. Data were taken by interviewing the informants who know well about Talaud language and can speak Talaud language fluently. The result of this research shows that the kinship terms in both languages are divided into consanguineal and afinal terms which are differentiated between sex, level of generation, lineage and age. Similarities in terms of sex namely, â€˜fatherâ€™ in English and â€˜iamanâ€™ in Talaud language and the similarities of generation for example in English â€˜brotherâ€™ and â€˜turran esaâ€™ in Talaud language. Sex in English and Talaud language is very important things to know because there are some variety of different terms to express differences in the sex of the relatives concerned. Lineage in English and Talaud language refers to the collateral only because the relatives are from the same ancestor but do not from one direct descendent. The difference between two languages is that the principle of age is not too important thing in English, but it is very important in Talaud Language to distinguish the older and the younger. Kinship term in English is not only refers to one relative but also to greet a priest and pastor, but in Talaud language it is not. Kinship term in English has four generations above and below ego, while in Talaud language has three generations above and below ego. Key Words : Kinship Terms, English and Talaud Language, Contrastive Analysis